Enhancing Stud Arc Welding Technique Vai Utilizing FuzzyLogic Approach (FLA) - Nabeel K. Abid AL-Sahib (Al-Khawarizmi Engineering Journal, 2013)
A fuzzy logic approach (FLA) application in the process of stud arc welding environment was implemented under the condition of fuzziness input data. This paper is composed of the background of FLA, related research work review and points for developing in stud welding manufacturing. Then, it investigates thecase of developingstud arc welding process on the controversial certaintyof available equipment and human skills.Five parameters (welding time, sheet thickness, type of coating, welding current and stud shape) were studied.A pair of parameter was selected asiteration whichis welding current and welding time and used for verification corresponding with tensile strength as output results and this willconsider it as schema for other cases.The testing result in the case of crisp (exact) value verifyingied the uncertainty value of some criteria selected which open the concept to make the decision making process for some advance cases without implementation. This paper applied the proposed methodology using Matlab program, the graphic user interface (GUI) fuzzy tool box for the case study of screw DABOTEKSTUD welding machine, for 6 mm diameter stud. The sheet materials are (K14358 and K52355) according to (USN standards, and the stud materials are (54NiCrMoS6 and 4OCrMnMoS8-6) according to (DIN standards).This given information is very inevitable for the conventional crisp determination of the tensile stress for the particular specimens experimented and also for verifying the tensile test value estimate in the case of changing to a fuzzy value for two of the input variables.